Comparative Study of Occurrence of Gastrointestinal Parasites in Tho-Tho and Cross-bred Cattle’s of Nagaland - CHAMUAH, J. K.; BORKOTOKY, D. (Indian Journal of Hill Farming, 2015)
A total of 90 animals each of both Tho-Tho and cross bred cattle were screened for the presence of gastrointestinal helminth parasites in and around the locality of Nagaland during the year of 2012-13. Among strongyle parasites, recorded parasites were Trichostrongylus, Haemonchus, Oesophagostomum and Cooperia species in both Tho-Tho cattle as well as cross bred. However, occurrence of Toxocara vitulorum and Bunostomum and Eimerian species were also recorded from calves. Among tapeworm infestation, M. benedeni was recorded in Tho-Tho and M. expansa was recorded in cross bred. As a whole, there was low level of subclinical infestation due to peculiar topography and climate of this region.